2007
DOI: 10.1177/1077546307077500
|View full text |Cite
|
Sign up to set email alerts
|

On Set-oriented Numerical Methods for Global Analysis of Non-smooth Mechanical Systems

Abstract: A large number of engineering systems include non-linear or even non-smooth behaviour. During development and optimisation of mechanical systems, a comprehensive dynamical analysis may be essential. Set-oriented Numerical Methods offer a new and efficient approach to global dynamical analysis without the requirement for a detailed a priori knowledge of the system dynamics. This paper shows the basic concepts behind this method and presents its application to a simple model of a vibro-impact device for ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The nonlinear dynamic characteristics of USDC were studied at the University of Paderborn in Germany, and it was found that there is a wobble phenomenon when using a disk‐shaped mass motion. The final design replaces the disk‐shaped free mass with a free spherical mass, which solves the wobble phenomenon (Neumann & Sattel, 2007; Neumann, Sattel, & Wallaschek, 2007; Potthast et al, 2007). In Figure 8h, Honeybee Robotics developed an ultrasonic penetrator Auto‐Gopher II.…”
Section: Research Status Of Planetary Penetratorsmentioning
confidence: 99%
“…The nonlinear dynamic characteristics of USDC were studied at the University of Paderborn in Germany, and it was found that there is a wobble phenomenon when using a disk‐shaped mass motion. The final design replaces the disk‐shaped free mass with a free spherical mass, which solves the wobble phenomenon (Neumann & Sattel, 2007; Neumann, Sattel, & Wallaschek, 2007; Potthast et al, 2007). In Figure 8h, Honeybee Robotics developed an ultrasonic penetrator Auto‐Gopher II.…”
Section: Research Status Of Planetary Penetratorsmentioning
confidence: 99%
“…For instance, the set-oriented method is applied to a simple nonsmooth mechanical model of an ultrasonic/sonic drilling device. Due to the complex dynamical behavior of the system, it is rather difficult to find periodic solutions by integrating the model, or to extract information from only a few long-term integrations (Neumann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are cases where such approaches are difficult to apply or even fail. This could be the case for systems with small or complicated attractors, making it difficult to find fixed points or periodic solutions (Neumann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%